The Environmental Relationships And Team Cooperation To Effectiveness Job Satisfaction - Galuh, Iman Rais Juliawan; Mulyanto, Agus Iwan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
Work Environment and Teamwork in increasing the job satisfaction of Tutoring lecturers in Serpong with quantitative descriptive methods, the analysis refers to the job satisfaction of the lecturers. The instrument used in data collection was a questionnaire. The results of this study indicate that the relationship between work environment and job satisfaction is very significant, the relationship between teamwork and job satisfaction is significant and finally, the relationship between work environment and teamwork collectively on lecturer job satisfaction has a regression line equation. can test correctively. Therefore, this correlation must be maintained and developed to achieve a better relationship so that it provides benefits for teachers and institutions, because there are more and better relationships, so that job satisfaction is higher. Keywords: Satisfaction, Environment, Team Work